2015
DOI: 10.1007/978-3-319-18179-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Customers’ Complaint Channel Choice and Complaint Behaviour

Abstract: This chapter introduces two empirical studies to analyse the adequacy of complaint channels. In detail, five communication channels (mail, e-mail, phone, face-to-face and social networks) as complaint channels are examined from a customer perspective with regard to five dimensions: procedural justice, interactional justice, distributive justice, personal attitudes and social interaction. First, to test the adequacy of the complaint channels, a one-way analysis of variance is conducted for each dimension identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…They examined the traditional communication channels telephone, face to face, mail, and email. Generally, these communication channels are suitable for making a complaint [15]. Mattila & Wirtz [12] revealed that the choice of communication channels depends on customers' motivation when voicing a complaint.…”
Section: Introductionmentioning
confidence: 99%
“…They examined the traditional communication channels telephone, face to face, mail, and email. Generally, these communication channels are suitable for making a complaint [15]. Mattila & Wirtz [12] revealed that the choice of communication channels depends on customers' motivation when voicing a complaint.…”
Section: Introductionmentioning
confidence: 99%